SH2‐Containing Inositol 5′‐Phosphatase 2 Selectively Impairs Hypothalamic Insulin Signalling and Regulation of Food Intake in Mice. (21st March 2013) - Ichihara, Y.; Wada, T.; Soeda, Y.; Ishii, Y.; Sasahara, M.; Tsuneki, H.; Sasaoka, T.
<x xml:space="preserve">Abstract</x> SH2‐containing inositol 5′‐phosphatase 2 (SHIP2) is a lipid phosphatase that negatively regulates the metabolic signalling of insulin in peripheral tissues; however, the expression of SHIP2 in the hypothalamus and its functional roles are largely unknown. In the present study, immunohistochemical analysis demonstrated that SHIP2 protein exists in neuronal cells expressing neuropeptide Y and pro‐opiomelanocortin in the arcuate nucleus of the hypothalamus in C57BL/6J mice. Interestingly, the expression levels of SHIP2 in the hypothalamus were elevated in aged C57BL/6J mice and diabetic db/db mice. To clarify the significance of the increased expression of SHIP2 in the hypothalamus, we examined the central effects of insulin and leptin in transgenic mice overexpressing SHIP2 (SHIP2‐Tg). Accumulation of phosphatidylinositol (3, 4, 5)‐trisphosphate and phosphorylation of Akt in the hypothalamus, induced by i.c.v. injection of insulin, were attenuated in SHIP2‐Tg compared to wild‐type mice, whereas leptin‐induced phosphorylation of signal transducer and activator of transcription 3 in the hypothalamus was comparable between them. The suppression of food intake after i.c.v. administration of insulin (but not leptin) was attenuated consistently in SHIP2‐Tg. In addition, SHIP2‐Tg showed increased food consumption after starvation and become heavier with visceral fat accumulation than wild‐type mice, despite normal levels of oxygen consumption and spontaneous movement. These results suggest that SHIP2 contributes to the regulation of food intake mainly via the attenuation of insulin signalling in the hypothalamus of mice.